2016
DOI: 10.1016/j.ygyno.2016.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Novel epigenetic changes in CDKN2A are associated with progression of cervical intraepithelial neoplasia

Abstract: Objective To conduct a comprehensive mapping of the genomic DNA methylation in CDKN2A, which codes for the p16INK4A and p14ARF proteins, and 14 of the most promising DNA methylation marker candidates previously reported to be associated with progression of low-grade cervical intraepithelial neoplasia (CIN1) to cervical cancer. Methods We analyzed DNA methylation in 68 HIV-seropositive and negative women with incident CIN1, CIN2, CIN3 and invasive cervical cancer, assaying 120 CpG dinucleotide sites spanning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 48 publications
0
28
0
1
Order By: Relevance
“…also induce dysfunction of oncogene and TSG, which are observed in kinds of cancers (Grønbæk et al, 2007; Singh et al, 2016; Wijetunga et al, 2016). Many studies showed that the collaboration of epigenetic and genetic changes is critically vital to drive the cancer development and progression (Baylin and Jones, 2016).…”
Section: Functions and Functional Synergy Of Oncogene And Tsgmentioning
confidence: 99%
“…also induce dysfunction of oncogene and TSG, which are observed in kinds of cancers (Grønbæk et al, 2007; Singh et al, 2016; Wijetunga et al, 2016). Many studies showed that the collaboration of epigenetic and genetic changes is critically vital to drive the cancer development and progression (Baylin and Jones, 2016).…”
Section: Functions and Functional Synergy Of Oncogene And Tsgmentioning
confidence: 99%
“…This is an expanding area where global cellular and/or viral changes including hypomethylation and hypermethylation are being investigated as diagnostic tools for detection of cervical precancerous lesions [47,7881]. Determining methylation levels on HR-HPV genomes has the potential to detect precancerous lesions with higher specificity than HPV testing alone [26].…”
Section: Potential New Biomarkers To Further Stratify Hpv-positivmentioning
confidence: 99%
“…Ongoing efforts will continue to require large prospective clinical studies to validate sensitivity, specificity, positive and negative predictive values for new techniques such as NGS that have been shown to be accurate and are becoming more cost-effective, where computational advances allow for increased sensitivity and depth of sequencing [83]. Further research on how changes in the viral and host methylome are associated with cervical cancer development should provide mechanistic insights facilitating prevention and treatment [74,81]. …”
Section: Potential New Biomarkers To Further Stratify Hpv-positivmentioning
confidence: 99%
See 2 more Smart Citations